Food babe kitchen : more than 100 delicious, real food recipes to change your body and your life - Hari, Vani (Hay House, Inc., 2020)
"Ditch processed foods and eat the cleanest, healthiest food on the planet by stocking your pantry, shopping, and cooking with Food Babe Kitchen. Over 100 mouthwatering recipes from Baja Fish Tacos and Grapefruit Goddess Salad to Rainbow French Fries and an 8-Minute Candy Bar will show readers how delicious and simple it is to eat healthy, easy, real food. Food Babe Kitchen shows you how to shop for the healthiest ingredients by breaking down every aisle in the grocery store with expert label-reading tips and simple swaps, plus a handy pantry list to stock your kitchen for success. Easy-to-follow directions, eye-catching photography, and simple substitutions to accommodate vegan, dairy-free, grain-free, and other diets, make this the ultimate guide to getting back into the kitchen to create healthful meals for yourself and those you love. Getting off processed food has never been easier - or more delicious. "I hope to inspire people to cook in a way of life that has dramatically improved my health, energy levels, and weight. I cannot wait to share what's cooking in my kitchen with the world!" - Vani Hari"--